THE ANTHROPOCENTRIC ESSENCE OF EMOTIVE PHRASEOLOGICAL UNITS IN EPISTOLARY DISCOURSE - Takhirova Nargiza Bakhtiyorovna (Modern American Journals, 2025)
This article is devoted to the study of the anthropocentric essence of emotive phraseological units in epistolary discourse. The research explores the role of idiomatic expressions as carriers of emotional meaning and cultural values in personal correspondence. Special attention is given to the universal and culture-specific aspects of phraseological expressions and their use in both traditional handwritten and modern digital correspondence. The article concludes that emotive phraseological units not only enrich the stylistic and emotional level of epistolary texts but also serve as powerful tools of anthropocentric reflection, connecting human emotions, cultural traditions, and interpersonal communication.
Keywords: epistolary discourse, phraseological units, emotive idioms, emotional communication, cultural specificity, identity expression.